Upaya Meningkatkan Perkembangan Kognitif Anak Melalui Kegiatan Menyusun Puzzle di TK Negeri Teratai Putih Desa Sungai Manau - Husna, Husna; Qalbi, Zahratul; Putera, Rafhi Febryan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to improve children's cognitive development through puzzle-assembling activities at the Teratai Putih State Kindergarten, Sungai Manau Village. The method used is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation and reflection stages. The research subjects were 19 children, and data was collected through observation, interviews and documentation, then analyzed descriptively qualitatively. The results showed a significant increase in children's cognitive development from cycle I to cycle II. In cycle I, the first meeting showed that 47.37% of children were in the Not Yet Developing (BB) category and 52.63% of children were in the Starting to Develop (MB) category. At the second meeting, there were no children in the BB category, with 84.21% of children in the MB category and 15.79% of children in the Developed (SB) category. In cycle II, the third meeting showed 42.11% of children in the MB category and 57.89% of children in the SB category. This research concludes that puzzle-building activities are effective in improving children's cognitive development, providing strong cognitive stimulation, and involving children in activities that require concentration, problem solving, and logical thinking. Thus, the use of puzzle media in the Teratai Putih State Kindergarten in Sungai Manau Village has proven successful in significantly increasing children's cognitive development.